Antifungal activity of Bacillus spp. against Fusarium oxysporum f. sp. lycopersici and Ascochyta sp. - Pelias Rafanomezantsoa; Samia Gharbi; Noureddine Karkachi; Mebrouk Kihal (Journal of Plant Protection Research, 2022)
The aim of this study is to find bacterial strains with antagonistic effects against Fusarium oxysporum f. sp. lycopersici ( Fol) and Ascochyta sp, which are phytopathogens responsible for fusarium wilt of tomato and ascochyta blight of peas, respectively. One hundred thirty- six bacteria isolated from the rhizosphere of tomatoes were screened. Five strains with the largest inhibition zones were selected. These strains were identified by the phenotypic method, later confirmed by sequencing of 16S rDNA. All strains belonged to the genus Bacillus spp. Their inhibition capacity was evaluated by the direct method by doing a dual culture, the inhibition rates ranged from 44.32 ± 0.8 to 61.36 ± 0.2 against Fol and 62.04 ± 0.8 to 74.1 ± 0.2% against Ascochyta sp. They were then evaluated by the indirect method by evaluating, on one hand, the antifungal effect of the volatile compounds produced by the strains and on the other hand, the antifungal effect of the filtrates. The results showed that volatile compounds inhibited plant pathogens’ growth with average inhibition rates of 55% against Fol and 17% against Ascochyta. For filtrates, the average inhibition rates were 33.01% against Fol and 33.74% against Ascochyta sp. Finally, the plant growth promoting rhizobacteria (PGPR) effect of B. halotolerans RFP57 was evaluated. This involved assessing their ability to stimulate the germination of tomato seeds and the growth of their vegetative organs. The results showed significant improvement in treated seedlings compared to controls. All these results show that the strains selected for this study have the potential for use as a biocontrol agent. However, it is clear that further in-depth studies are needed to confirm their true potentiality.